God-optional religion in twentieth-century America: Quakers, Unitarians, Reconstructionist Jews, and the crisis over theism - May, Isaac Barnes (Oxford scholarship online, 2023)
'God-Optional Religion in Twentieth-Century America' provides a historical account of the idea that being religious and believing in God might be separate concepts. Isaac Barnes May focuses on the story of three groups-liberal Quakers, Unitarians, and the forerunners of what would become Reconstructionist Judaism - and how they attempted to preserve their faith in the modern world by redefining what it meant to be religious.